Electrical Detection of Magnetic Skyrmions in a Magnetic Tunnel Junction. (23rd September 2022) - Guang, Yao; Zhang, Like; Zhang, Junwei; Wang, Yadong; Zhao, Yuelei; Tomasello, Riccardo; Zhang, Senfu; He, Bin; Li, Jiahui; Liu, Yizhou; Feng, Jiafeng; Wei, Hongxiang; et al.
Abstract: Magnetic skyrmions are promising information carriers for dense and energy‐efficient information storage owing to their small size, low driving‐current density, and topological stability. Electrical detection of skyrmions is a crucial requirement to drive skyrmion devices toward applications. The use of a magnetic tunnel junction (MTJ) is commonly suggested for this purpose as MTJs are key spintronic devices for large‐scale commercialization that can convert magnetic textures into electrical signals. To date, however, it has been challenging to realize skyrmions in MTJs due to incompatibility between standard skyrmion materials and highly efficient MTJ electrodes. Here, a material stack combining magnetic multilayers, which host 100 nm scale skyrmions, with a perpendicularly magnetized MTJ, is reported. The devices are designed so that the skyrmions in the multilayer are imprinted into the MTJ's free layer via magnetostatic interactions. The electrical response of a single skyrmion is successfully identified by employing simultaneous imaging of the magnetic texture and the electrical measurement of the MTJ resistance. The results are an important step toward all‐electrical detection of skyrmions. Abstract : An approach to tailor the skyrmion‐host material and magnetic tunnel junction (MTJ) is proposed, and the skyrmion in the host material can be successfully imprinted into the free layer of MTJ and read out via the tunneling magnetoresistance. This work demonstrates a highly efficient scheme to detect magnetic skyrmions with MTJ via spin texture imprinting.